Patterns of coexistence of six anemonefish species around subtropical Okinawa-jima Island, Japan - Hayashi, Kina; Tachihara, Katsunori; Reimer, James Davis (Coral reefs, 2018)
The species diversity of anemonefish in tropical regions has been explained by the niche differentiation hypothesis or cohabitation hypothesis. However, anemonefish community structure has seldom been investigated in high-latitude areas. To understand the mechanism underlying species diversity of anemonefish in the northern limits of their distribution and to compare with previous results from tropical and other areas, we investigated the community structure of anemonefish around the western coast of Okinawa-jima Island, Japan. Seven species of host anemones and six species of anemonefish were distributed across the 12 study sites. The diversity index of anemonefish and the host anemone varied among sites; anemonefish diversity increased with diversity of host anemones, which was associated with the ratio of sandy areas and distance from shore. The density of each species of anemonefish increased with the density of the primary host anemone, which suggests that niche differentiation may be occurring. However, results of two species of host anemone ( Stichodactyla mertensii , Heteractis magnifica ) associated each with two species of anemonefish did not support the niche differentiation hypothesis. Forty-seven percent of S. mertensii were shared by Amphiprion clarkii and A. sandaracinos simultaneously, supporting the cohabitation hypothesis. Amphiprion ocellaris and A. perideraion used the same host H. magnifica , but never shared a host simultaneously. Moreover, anemone size and water depth did not differ between the two anemonefish species, suggesting the possibility of the lottery model. In subtropical Okinawa, 86.7% of species interactions supported the niche differentiation hypothesis, 6.7% supported the cohabitation hypothesis, and 6.7% supported the lottery hypothesis. The mechanisms of coexistence of anemonefish in subtropical regions include not only niche differentiation and cohabitation but also the lottery hypothesis, which has not been reported in tropical regions.